Construction and test of an electric clock - Adams, Harvey (My University, 1905)
Inroduction: When the pendulum was first used to measure time the beats were counted by an attendant and time computed by that means. Someone then conceived the idea of a mechanism to record the beats and finally power in the shape of a suspended weight was used to maintain the motion of the pendulum. Since weights or springs are the ordinary means of storing the force necessary to run the clock -- which for convenience' sake should not require winding oftener than once in twenty-four hours -- they must be made heavy in the one case and in the other, strong. This power is conveyed by a number of "train" wheels to the "escape" wheel which revolves, in the ordinary clock from sixty to three hundred and sixty times an hour. Naturally this development of speed occasions friction with consequent loss of power in the transmission. This is particularly true when the lubricating oil becomes stiff by long exposure to air or deposits of dust. Then in this condition a fall of temperature, by farther stiffening the lubricant, stops the clock. Now if by some means a. force sufficient to keep it oscillating, could be applied directly to the pendulum, by this means turning the train -wheels carrying the hands, a great saving in friction and in variation would result, for the train -wheels would not be carrying power as in an ordinary clock but would carry only the weight of the hands. Electricity seems to present a solution of the troubles of clock makers but so far has been little used. It has been and is used in two different ways:- independently, that is a motive power; and as a means of connecting one timepiece with a number of dials which are so contrived that their hands move with the central timepiece.
Citation: Adams, Harvey. Construction and test of an electric clock. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Electromagnets; Escape-Wheel; Train-Wheels; Theses